2021
DOI: 10.3390/jmse9060591
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Sub-Fossil Diatoms Flora in the Sediments of Suncheonman Bay, Korea

Abstract: Suncheonman Bay, Korea’s most representative estuary, is an invasive coastal wetland composed of 22.6 km2 of tidal flats surrounded by the Yeosu and Goheung Peninsulas. In January 2006, this region was registered in the Ramsar Convention list in Korea, representing the first registered wetland. Estuaries are generally known to have high species diversity. In particular, several studies have been conducted on planktonic and epipelic diatoms as primary producers. Suncheonman Bay has already been involved in many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 109 publications
0
11
0
Order By: Relevance
“…nov., was initially reported as an unidentified species (Giffenia sp.) in a previous study (Park et al 2021). Subsequently, the species was confirmed to be novel through extensive electron microscopic analyses and a review of references.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…nov., was initially reported as an unidentified species (Giffenia sp.) in a previous study (Park et al 2021). Subsequently, the species was confirmed to be novel through extensive electron microscopic analyses and a review of references.…”
Section: Discussionmentioning
confidence: 74%
“…nov. is found in all sections from 0.1 m to 6.0 m at 0.5 m intervals in core SCW03, both in this study and the previous report (as Giffenia sp.) (Park et al 2021). Considering the AMS age-dating results of core SCW03 (Park et al 2021), this species, identified as G.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Park et al [6] investigated fossil diatoms in Suncheonman Bay and introduced subfossil diatoms recorded in Korea. One sedimentary core has been extracted in 2018.…”
Section: Papers Detailsmentioning
confidence: 99%